Detection and evaluation of predisposing factors for the presence of spondylolysis and spondylolisthesis in adolescent athletes - a systematic review - Joost, T.; Engel, T.; Cassel, M. (Sport-Orthopädie - Sport-Traumatologie, 2022)
Summary Background